THE MOROCCAN WAQF AND THE COMMON-LAW TRUST: A COMPARATIVE STUDY (UUM Journal of Legal Studies, 2022)
Etymologically, the term trust originates from Latin; it means “care”. Charitable trusts and waqfs are methods of facilitating the intergenerational management of family wealth. Both are thought of as estate-planning vehicles, ensuring that assets of the testate go to certain individuals or organizations. However, whereas the trust has expanded its scope to cover the economic field, the waqf in Morocco is still considered a religious exercise. While there are shared features between the Moroccan waqf and the trust, they are conceptually and practically different in many aspects, most importantly in their perception of ownership and their contrasting stances regarding endowment duration. Despite the importance of the  trust. The comparative legal methodology has been adopted to study the spirit of the different legal systems. The comparison has revealedthe existence of undeniable similarities in terms of the management of endowments, yet the differences are numerous, especially with regard to ownership structure, juristic personality, and perpetuity rules, among others